Experimental Study on Bond Behavior between Rusty Steel Reinforcement and Concrete - Majed A. Khalaf; Fareed H. Majeed (Tikrit Journal of Engineering Sciences, 2018)
The effect of rust of the reinforcement bars on the bond and slip behavior between the rebars and the surrounding concrete is still under research judgement. This paper, investigated the effect of ranges of rebar rusting (0, 30-50% and 70-90%) of the limits of losing in mass that specified in the ASTM standard (6% of bar nominal mass) combined with other main parameters that affect the bond and slip behavior. A number of 72 pullout prepared specimens were tested. The studied parameters were using normal and high strength concrete (31 MPa and 76 MPa), different bars diameters (12, 16 and 25 mm), the change of embedment length (150 and 300 mm) and the using of bond epoxy coating for embedded length of reinforcing bars. The results showed that the rust within certain amount of permissible losing of mass (about 50%) led to increase the bond strength and decrease the slip between reinforcement bars and concrete. However, increasing rusting above 50% but within the permissible losing in mass would slightly decrease the bond strength and increase the slip comparing with zero rusting case for all tested bar sizes with and without using the bond improvement factors. The main recommendation of the study is to use the same criterion of acceptance of losing in mass specified by ASTM as the acceptance criterion of the amount of rust in the reinforcement bars and using one of the studied improvement factors when the rust amount exceed 50% of the permissible limit of losing in mass.